Cordyceps militaris extract and cordycepin ameliorate LPS-challenged colonic damage in piglets by modulating the microbiota and metabolite profiles - Xiong, Shijie; Wan, Fan; Jiang, Jiajia; Liu, Yanfang; Hang, Yiqiong; Xue, Huiqin; Lu, Yang; Su, Yong (Frontiers in Immunology, 2025)
IntroductionCordyceps militaris extract (CME) and cordycepin (CPN) are biomolecules with a wide range of biological activities, including anti-inflammatory, antioxidant and anti-tumour effects. The research objective wasto investigate the influences of CME and cordycepin CPN on colonic morphology, microbiota composition and colonic metabolomics in lipopolysaccharide (LPS)-challenged piglets.MethodsTwenty-four weaned castrated piglets were randomly divided into four groups: control group (fed basal diets), LPS group (fed basal diets), CPN-LPS group (basal diets + 60 mg/kg cordycepin), and CME-LPS group (basal diets + 60 mg/kg C. militarisextract). On the 21st day, the LPS, CPN-LPS, and CME-LPS groups received an injection of 100 μg/kg BW LPS, while the control group was given sterile saline.ResultsThe findings demonstrated that CPN or CME attenuated intestinal morphology damage with LPS-challenged piglets. CPN and CME alleviated intestinal microbiota dysbiosis and metabolic disorders under LPS-challenged by enriching serum protein levels, regulating of inflammatory cytokine secretion and altering colonic microbial composition. Colonic microbiota analysis that the CPN improved the relative abundance of Acidobacteriota and inhibited Faecalibacterium, CME promoted the relative abundance of Prevotella and Lachnospiraceae NK4A136group. Meanwhile, the alleviation of colonic damage is achieved through modulation of metabolic pathways linked to tryptophan metabolism, biosynthesis of amino acids and butanoate metabolism.DiscussionConclusively, our preliminary findings reveal that CPN or CME could serve as a beneficial dietary supplement to alleviate gut diseases in weaning piglets.